2020
DOI: 10.3390/app10041341
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Method for Controlling the Asymmetric Mode of Atmospheric Dielectric Barrier Discharges

Abstract: Atmospheric pressure dielectric barrier discharges (DBDs) have been applied in a very broad range of industries due to their outstanding advantages. However, different discharge modes can influence the stability of atmospheric DBDs, such as the density and composition of active species in discharge plasmas, thereby impacting the effect of related applications. It is necessary and valuable to investigate the control of nonlinear modes both in theoretical and practical aspects. In this paper, we propose a practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In addition, it can be observed from the photos in Figure 4 and Figure 5 that, except for the filaments in Figure 5 a, which are in a state of random migration, the whole plasma slowly moves down with the flow of the discharge gas, and the positions of the filaments are relatively fixed. On the other hand, it can be seen from the waveforms shown in Figure 11 that the current waveform of RF-DBD is smooth, which is different from the current waveform of middle-frequency DBD [ 23 ]. Therefore, it can be concluded that the filaments are not extinguished during one period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can be observed from the photos in Figure 4 and Figure 5 that, except for the filaments in Figure 5 a, which are in a state of random migration, the whole plasma slowly moves down with the flow of the discharge gas, and the positions of the filaments are relatively fixed. On the other hand, it can be seen from the waveforms shown in Figure 11 that the current waveform of RF-DBD is smooth, which is different from the current waveform of middle-frequency DBD [ 23 ]. Therefore, it can be concluded that the filaments are not extinguished during one period.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies show that, compared with bare electrodes, dielectric barrier discharge (DBD) allows plasma to retain its large volume without constriction [ 15 , 16 , 20 ]. Among the various power sources used in atmospheric DBD discharge [ 9 , 21 , 22 , 23 , 24 ], RF power shows unique advantages in low breakdown voltage, stability and power density improvement [ 9 , 20 , 25 , 26 ]. On the other hand, filamentous discharge as a common discharge mode of DBD has also been studied a lot [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [2] developed a practical method for controlling the switch been the symmetric and asymmetric modes of a dielectric barrier discharge at atmospheric pressure by changing the frequency of the applied voltage. In this work, through a qualitatively validated 1D fluid model, the discharge evolution, manipulating process and underlying mechanism are also presented.…”
Section: Plasma Sourcesmentioning
confidence: 99%
“…On the other hand, radio frequency DBD is now a popular source used to achieve a stable and large-gap atmospheric pressure glow discharge with lower breakdown voltage and avoid emergence of arc discharge and filamentary discharge, compared with DC glow discharge and low and medium frequency DBD at atmospheric pressure [6][7][8][9][10][11]. Therefore, a lot of study has been done on the discharge mechanism, simulation, and speckle pattern of radio-frequency dielectric barrier discharge (rf-DBD) at atmospheric pressure [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%